Sunnatullah Dalam Kisah Musa Dan Fir’aun - Moh. Mauluddin (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
In general, sunnatullah is understood as a provision of Allah that does not change, and is associated with the consistency of nature, such as the alternation of day and night, the passage of the sun, the rotation of the earth, water flowing from a high place to a lower place, rain falling from the sky, and so on. In fact, the verses regarding sunnatullah are all related to human behavior in social life. Or it can be said that sunnatullah is actually God's law (God's provisions) that applies in the social life of society. According to Taqī Misbāh al-Yazdi, a philosopher and professor at the Center for Islamic Studies in Iran, sunnatullah is essentially God's punishment imposed on society. Therefore, this study will review these problems using the thematic method by raising one of the stories in the Qur'an, namely the story of Moses and Pharaoh. According to Mannaaal-Qattan, qissah Al-Qur'an is information or events regarding the condition of the previous people and the previous prophets are also events that really happened. Therefore, the stories in the Qur'an are closer to the meaning of events than other meanings. As we all know, events are the human past that cannot be reconstructed, because the human past cannot be replayed. From this study, there are at least two objectives, namely 1) obtaining correct and comprehensive knowledge about sunnatullah, 2) correcting a person's cognitive knowledge, if it turns out that he is not the same as what the Qur'an wants it to be.